2022
DOI: 10.1097/aln.0000000000004262
|View full text |Cite
|
Sign up to set email alerts
|

Isoelectric Electroencephalography in Infants and Toddlers during Anesthesia for Surgery: An International Observational Study

Abstract: Background Intraoperative isoelectric electroencephalography (EEG) has been associated with hypotension and postoperative delirium in adults. This international prospective observational study sought to determine the prevalence of isoelectric EEG in young children during anesthesia. We hypothesized that the prevalence of isoelectric events would be common worldwide and associated with certain anesthetic practices and intraoperative hypotension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Emergence agitation occurs usually within the first 30 min after anesthesia, and is characterized by combativeness, excitation, disorientation, and inconsolability [ 33 ]. In a single- and in a multi-center study in children up to 37 or 36 months of age, respectively, isoelectric events during anesthesia were not associated with emergence behavior [ 34 , 35 ]. After anesthesia with the inhalation anesthetic sevoflurane, which was given in our study, emergence delirium occurs particularly frequently in children [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emergence agitation occurs usually within the first 30 min after anesthesia, and is characterized by combativeness, excitation, disorientation, and inconsolability [ 33 ]. In a single- and in a multi-center study in children up to 37 or 36 months of age, respectively, isoelectric events during anesthesia were not associated with emergence behavior [ 34 , 35 ]. After anesthesia with the inhalation anesthetic sevoflurane, which was given in our study, emergence delirium occurs particularly frequently in children [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the BIS represents the level of consciousness under anesthesia, which has proven controversial among anesthesiologists ( 31 , 32 ). Intraoperative isoelectric electroencephalography (EEG) has been considered to be associated with delirium in many studies ( 33 , 34 ), however, two recent studies of isoelectric EEG in toddlers or older adults showed that it was not independently correlated with ED ( 35 , 36 ). More high-quality RCT trials are needed to confirm BIS- or EEG-guided anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…At discharge from operatory room, patients showed a median PAED score of 11. [10][11][12] The presence of a BS episode was not associated with the PAED levels (OR 1.58, 95% CI 0.14-16.74, p = .18). Shorter surgeries were associated with higher PAED levels (r: −.36, 95% CI −0.55 to −0.13, p = .0025), and lower PSI at extubation (r: −.46, 95% CI −0.62 to −0.27, p < .0001).…”
Section: Re Sultsmentioning
confidence: 92%
“…4,9 This is because this technology is not routinary applied in pediatric anesthesia and the use of dedicated pediatric devices is still on a development phase. 4,[9][10][11][12] However, if feasible, a pEEG-guided anesthesia might contribute to optimally target anesthesia depth. The Root® and SedLine® monitor (Masimo Inc.) and the novel SedLine pediatric sensors (Masimo Inc.) can be applied as a pEEG monitor in children.…”
Section: Introductionmentioning
confidence: 99%